Trace detection of herbicides by SERS technique, using SERS-active substrates fabricated from different silver nanostructures deposited on silicon. (19th June 2015) - Dao, Tran Cao; Luong, Truc Quynh Ngan; Cao, Tuan Anh; Nguyen, Ngoc Hai; Kieu, Ngoc Minh; Luong, Thi Thuy; Le, Van Vu
Abstract: In this report we present the initial results of the use of different silver nanostructures deposited on silicon for trace detection of paraquat (a commonly used herbicide) using the surface-enhanced Raman scattering (SERS) effect. More specifically, the SERS-active substrates were fabricated from silver nanoparticles (AgNPs) deposited onto the flat surface of a silicon wafer (AgNPs@Si substrate), as well as on the surface of an obliquely aligned silicon nanowire (SiNW) array (AgNPs@SiNWs substrate), and from silver nanodendrites (AgNDs) deposited onto the flat surface of a silicon wafer (AgNDs@Si substrate). Results showed that with the change of the structure of the SERS-active substrate, higher levels of SERS enhancement have been achieved. Specifically, with the fabricated AgNDs@Si substrate, paraquat concentration as low as 1 ppm can be detected.